Fouling resistant nitrogen doped carbon powder with amino-tri-methylene-phosphate cathode for microbial fuel cell - Pratik Kumar; Pritha Chatterjee; M. M. Ghangrekar (Materials for Renewable and Sustainable Energy, 2017)
Abstract Long term stable performance of a microbial fuel cell (MFC) is difficult to achieve because of scale formation on cathode. Nitrogen doped carbon powder (NDCP) was used as cathode along with amino-tri-methylene-phosphate (ATMP) as an anti-scaling agent in a MFC. Maximum power density of 66 mW/m2 obtained in the MFC using NDCP as cathode, was 2.2 times higher than that obtained with simple carbon powder. High electroactive surface area and meso-porous structure of the NDCP improved electrochemical performance of the MFC having NDCP cathode. After 40 days of operation, the maximum power density decreased by only 12.5% in the MFC using NDCP and having ATMP in its cathode as compared to a 55.6% decrease in the MFC using only carbon powder in cathode due to fouling. Ultrathin shell structure of NDCP catalyst molecules, as evident from transmission electron microscopy (TEM) images, ensured high catalyst performance providing good electron transfer for enhancing oxygen reduction reaction (ORR). Less deposition of calcite molecules on cathode surface, illustrated via X-ray diffraction (XRD) after 40 days of operation, clearly reveals high anti-fouling property of ATMP as a cathode material. ATMP being a commercial anti-scaling agent has inherent chelation properties to stop chemical fouling and thus helped in demonstrating stable long term performance of cathode in the MFCs. NDCP along with ATMP could be used for fabrication of a cost effective fouling resistant cathode for long term use by increasing ORR in MFCs to achieve stable power generation by minimizing scale formation on cathode and effective wastewater treatment simultaneously. Graphical abstract